The Impact of High School Financial Education on Financial Knowledge and Choices: Evidence from a Randomized Trial in Spain - Olympia Bover; Laura Hospido; Ernesto Villanueva (Institute of Labor Economics (IZA), 2018)
We conducted a randomized controlled trial where 3,000 9th grade students coming from 78 high schools received a financial education course at different points of the year. Right after the treatment, test performance increased by 16% of one standard deviation, treated youths were more likely to become involved in financial matters at home and showed more patience in hypothetical saving choices. In an incentivized saving task conducted three months after, treated students made more patient choices than a control group of 10th graders. Within randomization strata, the main impacts are also statistically significant in public schools, which over-represent disadvantaged students.
Keywords: D14; D91; I22; J24; 330; financial education; impact evaluation